Impact of the Covid-19 Pandemic on the Financial Health of Nepalese Development Banks: A Comparative Analysis (The Lumbini Journal of Business and Economics, 2024)
Purpose: This research aims to evaluate the impact of the COVID-19 pandemic on the financial health of Nepalese development banks by comparing their financial ratios before and after the pandemic outbreak. It seeks to identify areas of strength and weakness enabling stakeholders to make informed decisions regarding the sector’s stability and prospects.Methods: Descriptive research design with a longitudinal comparative approach has been adopted. Financial ratios are calculated for six selected development banks for the period of 2017-2023. Mean ratios are computed for pre-COVID and post-COVID periods, and percentage changes are analysed using paired sample t-tests.Results: The analysis reveals significant differences financial ratios during the periods of pre and post-COVID including shifts in asset allocation, increased non-performing loans, reduced capital adequacy, improved market valuations, and decreased profitability ratios.Conclusion: The study demonstrates the pandemic’s wide-ranging impact on Nepal’s development banking sector, highlighting the need for effective risk management, capital planning, and strategic changes to maintain financial stability and to facilitate effective recovery.